PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN LEVERAGE SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN SUB SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Siallagan, Maria Emas P.; Siahaan, Yansen; Jubi, Jubi; Inrawan, Ady (SULTANIST: Jurnal Manajemen dan Keuangan, 2018)
The purposes of this research are to know the description of profitability, firm value, and leverage, to determine the effect of profitability on the value and to determine leverage ability to moderated profitability reletionships with firm value  at  Farmasi Sub-Sector Company listed on the Indonesia Stock Exchange. The research was conducted with qualitative descriptive analysis method and quantitative descriptive analysis. The data are collected  by using documentation method. The analysis technique used simple linear regression, moderation regression, correlation coefficient, determination coefficient and hypothesis test. Data are analysed with the help of SPSS version 20.          The results of this research be summarized as follows: 1. Average ROE fluctuated and tended to decline, the average DER fluctuated and tended to increase, and the average PBV fluctuated and tended to increase. 2. The results of simple linear regression test showed that profitability has negative effect on firm value. 3. The results of the moderation regression test showed that leverage weakens the profitability relationship with the value. 4. The results of testing the first hypothesis can be concluded that profitability has a negative effect not significant on firm value. 5. The results of the second hypothesis test can be concluded that leverage is  able to moderate the relationship between profitability and firm value.The research suggest that companies increase sales to optimize profits, use debt to increase company productivity, control the existing management of the company and distribute dividend to shareholders.